Resistance Inheritance of Plutellaxylostella Population to Residual of Emamectin Benzoat - Udi Tarwotjo; Rully Rahardian (Biosaintifika: Journal of Biology & Biology Education, 2017)
Excessive use of insecticides drives the increasing ability of pests to become resistant. The objectives of this research were to study the susceptibility and the resistance inheritance of the eleven population of P. xylostella to emamectin benzoate. The leaf-dip bioassay was applied to determine the sensitivity of P. xylostella to emamectin benzoate. The offspring of backcrossed F2 were tested whether the resistance was controlled by monogenic. The results showed that the LC50 of the Selo population was 53.42 ppb, and the Puasan population was 212.13 ppb. The genetic analysis showed that the backcrosseddegree of dominance (D) was less than 1. It was indicated that the P. xylostella resistance to emamectin benzoate was recessive. The value of LC50 of the backcrossed F1♀ x ♂S (177.99 ppb) and its reciprocals x ♀R (F1) (201.69 ppb) were not significantly different with the value of LC50 resistance population. This suggests that the nature of P. xylostella resistance to emamectin benzoate was controlled by monogenic.The result of the study would be beneficial for developing strategy to maintain susceptible population using refugee plant during lack of their host.